Early rhythm‐control ablation therapy to prevent atrial fibrillation recurrences: Insights from the CHARISMA Registry. Issue 12 (21st October 2021) - Solimene, Francesco; Giannotti Santoro, Mario; Stabile, Giuseppe; Malacrida, Maurizio; De Simone, Antonio; Pandozi, Claudio; Pelargonio, Gemma; Rossi, Pietro; Battaglia, Alberto; Pecora, Domenico; Bongiorni, Maria Grazia; Zucchelli, Giulio; et al.
Abstract: Background: An early, comprehensive rhythm‐control therapy is needed in order to treat atrial fibrillation (AF) effectively and to improve ablation outcomes. Methods: A total of 153 consecutive patients from the CHARISMA registry undergoing AF ablation at eight centers were included. Patients with de novo PVI were classified as having undergone early treatment (ET) if the procedure was performed within 6 months after the first AF episode, and as having undergone delayed treatment (DT) if ablation was performed over 6 months after the first AF episode. Results: One‐hundred fifty‐three patients were enrolled (69.9% male, 59 ± 10 years, 61.4% paroxysmal AF, 38.6% persistent AF). The time from the first AF episode to the ablation procedure was 1034 ± 1483 days. The ET group comprised 36 patients (25.3%), the DT group 60 (39.2%) and Redo cases were 57 (37.3%). During a mean follow‐up of 366 ± 130 days, 18 patients (11.8%) suffered an AF/AT recurrence. More DT patients than ET patients suffered recurrences (15.7% vs. 2.2%, p = 0.0452) and the time to AT/AF recurrence was shorter in the group of patients who received an ablation treatment after 6 months (HR = 6.19, 95% CI: 1.7 to 21.9; p = 0.0474). On multivariate Cox analysis, only hypertension (HR = 4.86, 95% CI: 1.6 to 14.98, p = 0.0062) was independently associated with recurrences. Beyond the hypertension risk factor, ET was associated with a low risk of recurrence; recurrence rate ranged from 0% (ET patients without hypertension) to 25.0% (DT patients with hypertension). Conclusions: An early rhythm‐control ablation therapy in the absence of common risk factors was associated with the lowest rate of recurrences.